Phenotypic and in silico studies for a series of synthetic thiosemicarbazones as New Delhi metallo-beta-lactamase carbapenemase inhibitors. Issue 24 (26th December 2022) - Moreira, Jonatham Souza; Galvão, Danilo Santana; Xavier, Carolina Ferreira Cavalcanti; Cunha, Silvio; Pita, Samuel Silva da Rocha; Reis, Joice Neves; Freitas, Humberto Fonseca de
Abstract: The past two decades have been marked by a global spread of bacterial resistance to β-lactam drugs and carbapenems derivatives are the ultimate treatment against multidrug-resistant bacteria. β-lactamase expression is related to resistance which demands the development of bacterial resistance blockers. Drug inhibitor combinations of serine-β-lactamase and β-lactam were successful employed in therapy despite their inactivity against New Delhi metallo-beta-lactamase (NDM). Until now, few compounds are active against NDM-producing bacteria and no specific inhibitors are available yet. The rational strategy for NDM inhibitors development starts with in vitro assays aiming to seek compounds that could act synergistically with β-lactam antibiotics. Thus, eight thiosemicarbazone derivatives were synthesized and investigated for their ability to reverse the resistant phenotype in NDM in Enterobacter cloacae . Phenotypic screening indicated that four isatin-beta-thiosemicarbazones showed Fractional Inhibitory Concentration (FIC) ≤ 250  µM in the presence of meropenem (4 µg/mL). The most promising compound (FIC= 31.25 µM) also presented synergistic effect (FICI = 0.34). Docking and molecular dynamics studies on NDM-thiosemicarbazone complex suggested that 2, 3-dihydro-1 H -indol-2-one subunit interacts with catalytic zinc and interacted through hydrogen bonds with Asp124 acting like a carboxylic acid bioisostere. Additionally, thiosemicarbazone tautomer with oxidized sulfur (thione) seems to act as a spacer rather than zinc chelator, and the aromatic moieties are stabilized by pi–pi and cation–pi interactions with His189 and Lys221 residues. Our results addressed some thiosemicarbazone structural changes to increase its biological activity against NDM and highlight its scaffold as promising alternatives to treat bacterial resistance. Communicated by Ramaswamy H. Sarma